2019
DOI: 10.1038/s41467-019-11631-w
|View full text |Cite
|
Sign up to set email alerts
|

Cellular internalization of bystander nanomaterial induced by TAT-nanoparticles and regulated by extracellular cysteine

Abstract: Entry into cells is necessary for many nanomaterial applications, and a common solution is to functionalize nanoparticles (NPs) with cell-penetrating ligands. Despite intensive studies on these functionalized NPs, little is known about their effect on cellular activities to engulf other cargo from the nearby environment. Here, we use NPs functionalized with TAT (transactivator of transcription) peptide (T-NPs) as an example to investigate their impact on cellular uptake of bystander cargo. We find that T-NP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 42 publications
7
56
0
Order By: Relevance
“…8). 195,313 Shortly after TAT-peptide discovery, a homeoprotein penetratin of fruit fly Drosophila melanogaster has also been shown to have the ability for transporting therapeutic molecules across the cell membrane. 314 More than 100 peptides have been used since then to accelerate therapeutics delivery, such as siRNA, 315 antisense oligomers, 316 enzymes, 317 etc.…”
Section: Bio-inspired Moleculesmentioning
confidence: 99%
“…8). 195,313 Shortly after TAT-peptide discovery, a homeoprotein penetratin of fruit fly Drosophila melanogaster has also been shown to have the ability for transporting therapeutic molecules across the cell membrane. 314 More than 100 peptides have been used since then to accelerate therapeutics delivery, such as siRNA, 315 antisense oligomers, 316 enzymes, 317 etc.…”
Section: Bio-inspired Moleculesmentioning
confidence: 99%
“…In this context, an increase in uptake of both gold and iron oxide particles has been described when the two particles are exposed together to J774A.1 murine macrophages [37]. Similarly, it has been reported that uptake of a number of different nanoparticles increases when the nanoparticles are exposed to cells together with functionalised nanoparticles [38,39]. An increased uptake has also been described in vivo when nanoparticles are simultaneously administered with nanoparticles self-assembled from amphiphilic peptides [40].…”
Section: Introductionmentioning
confidence: 79%
“…When nanomaterials are evaluated, this methodological procedure could cause a potential problem as Cyt-B also inhibits endocytosis processes-in which actin plays an essential role [44]-used by most cells to internalize nanomaterials [10,45]. Therefore, evaluating whether the presence of Cyt-B interferes with the cellular uptake of study NP is essential and very useful to interpret correctly the CBMN results obtained for these NP [6,[46][47][48][49]. In the present study, cellular uptake results confirmed an efficient dose-and time-dependent internalization of the TiO 2 NP by SH-SY5Y cells, regardless the Cyt-B concentration or its presence in the medium prior to the TiO 2 NP treatments.…”
Section: Discussionmentioning
confidence: 99%